Efektivitas Pendekatan Roleplay dalam Meningkatkan Partisipasi Siswa pada Pembelajaran Bahasa Arab di MTsN 1 Lamongan - Dimas Zonseta Tosan (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the effectiveness of the roleplay approach in enhancing students’ participation in Arabic language learning at MTsN 1 Lamongan. The research employed a quantitative method with a one-group pretest–posttest design. The subjects were 32 eighth-grade students selected through purposive sampling. The research instrument was a student participation observation sheet that had been tested for validity (r > 0.349) and reliability (α = 0.847). Data were analyzed using a paired sample t-test after conducting the Kolmogorov–Smirnov normality test. The results showed a significant increase in student participation, from an average score of 9.78 (pretest) to 14.84 (posttest), with a gain score of 5.06 points or a 51.7% improvement. The t-test results indicated that t-value = -14.908 > t-table = 2.040 with a significance level of p < 0.001, demonstrating a statistically significant difference. The effect size (Cohen’s d = 2.63) indicated a large impact. Qualitative findings revealed increased enthusiasm, reduced shyness, and improved peer-to-peer interaction. The roleplay approach proved effective for students across all initial ability levels. This study recommends the systematic integration of roleplay into Arabic language learning in madrasah. Keywords: Roleplay, Student Participation, Arabic Language Learning, Madrasah